توظيف وسيلة غطاء زجاجة الصندوق السحري (Magic Box Bottle Cap) لترقية استيعاب المفردات العربية لدى طلبة المدرسة المتوسطة - Basyori, Ahmad; Afijah, Nadya; Dinata, Rahmat Satria (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2025)
ملخص البحث: هدف هذا البحث إلى توظيف وسيلة غطاء زجاجة الصندوق السحري (Magic Box Bottle Cap) في تعليم المفردات العربية لدى طلاب الصف السابع "أ" في مدرسة الإخلاص المتوسطة الإسلامية بمنطقة تانجونج بينتانج، و تقييم مدى فاعلية هذه الوسيلة لترقية استيعاب المفردات . يندرج هذا البحث ضمن منهج البحث الإجرائي الصفي، وقد شمل طلاب الصف السابع "أ" في مدرسة الإخلاص المتوسطة الإسلامية بمنطقة تانجونج بينتانج كعينة للدراسة، بتوظيف أدوات تشمل الاختبار القبلي والاختبار البعدي. أما تقنيات جمع البيانات فقد تمثلت في الملاحظة، والمقابلة، والتوثيق، مع اعتماد نوعي البيانات الكمية والنوعية معًا. أظهرت نتائج البحث: 1) بعد توظيف وسيلة غطاء زجاجة الصندوق السحري توزّع على ثلاث فئات: الفئة المتوسطة شملت 7 طلاب (بنسبة 28٪)، والفئة العالية ضمّت 15 طالبًا (60٪)، بينما كان هناك 3 طلاب (12٪) في الفئة العالية جدًا. 2) شهدت نتائج الطلاب تحسنًا مستمرًا عبر دورتين تدريبيتين، حيث ارتفعت نسبة إتقان المفردات في اللغة العربية تدريجيًا، ويُعزى هذا التحسن إلى توظيف هذه الوسيلة. أما نسب الإتقان فقد بلغت 63٪ في المرحلة التمهيدية، ثم ارتفعت إلى 65٪ في الدورة الأولى، وصولًا إلى 82٪ في الدورة الثانية، مما يدل على تحسن ملحوظ في نتائج التعلم. الكلمات الأساسية : غطاء زجاجة الصندوق السحري ، استيعاب المفردات، وسيلة التعليم. Abstract: This research aimed to employ the Magic Box Bottle Cap media in teaching students Arabic vocabulary of Grade 7A at Al-Ikhlas Islamic Middle School in Tanjung Bintang, as well as to evaluate the effectiveness of this media in teaching the Arabic Vocabulary. This research falls within the classroom action research methodology, and included students of this school as a sample for the study, using tools including a pre-test and post-test. The data collection techniques were observation, interview, and documentation, with the adoption of both quantitative and qualitative data. The results of the research showed that students' performance was distributed into three categories: The medium category included 7 students (28%), the high category included 15 students (60%), and there were 3 students (12%) in the very high category. The students' results showed a continuous improvement over two training sessions, as the percentage of vocabulary mastery in Arabic gradually increased, and this improvement was attributed to the use of this method. Mastery rates reached 63% in the introductory phase, then increased to 65% in the first course, and reached 82% in the second course, indicating a significant improvement in learning outcomes. Keywords: Magic Box Bottle Cap, Vocabulary Mastery, Learning Media. Abstrak: Penelitian ini bertujuan untuk menerapkan media Tutup Botol Kotak Ajaib dalam pengajaran kosakata Arab bagi siswa kelas 7A di Madrasah Tsanawiyah Al-Ikhlas di Tanjung Bintang, serta mengevaluasi efektivitas media tersebut dalam pengajaran kosakata Arab. Penelitian ini menggunakan metodologi penelitian tindakan kelas, dengan sampel siswa sekolah tersebut, dan menggunakan alat ukur berupa pre-test dan post-test. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi, dengan penggunaan data kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa prestasi siswa terbagi menjadi tiga kategori: Kategori sedang mencakup 7 siswa (28%), kategori tinggi mencakup 15 siswa (60%), dan 3 siswa (12%) berada di kategori sangat tinggi. Hasil siswa menunjukkan peningkatan berkelanjutan selama dua siklus pelatihan, karena persentase penguasaan kosakata dalam bahasa Arab secara bertahap meningkat, dan peningkatan ini dikaitkan dengan penggunaan metode ini. Tingkat penguasaan mencapai 63% pada fase pengenalan, kemudian meningkat menjadi 65% pada kursus pertama, dan mencapai 82% pada kursus kedua, menunjukkan peningkatan signifikan dalam hasil belajar. Kata kunci: Tutup Botol Kotak Ajaib, Penguasaan Kosakata, Media Pembelajaran.